1993
DOI: 10.1111/j.1432-1033.1993.tb18376.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of the human inter‐α‐trypsin inhibitor heavy‐chain H1 gene

Abstract: The human inter-a-trypsin inhibitor heavy chain HI (IT1 heavy chain H1) gene was isolated from two overlapping clones. It spans 14 kbp and is composed of 22 exons from 15 bp to 281 bp in size and has consensus splice sites. Intron sizes range from 80 bp to 2000 bp. It codes for the precursor of HCI that is part of the serum IT1 form of 220 kDa. Two major transcriptional initiation sites were identified in the 5'-flanking region, which contained putative promoter elements, but no typical TATA and CAAT boxes. mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…6 plaques of a human genomic (leukocyte) library (CLONTECH) constructed in EMBL3 were screened by plaque hybridization with full-length ITI heavy chain cDNA probes labeled with 32 P by the random primer method. Hybridization was carried out as described by Maniatis et al (36).…”
Section: Screening Of the Human Genomic Library-10mentioning
confidence: 99%
See 1 more Smart Citation
“…6 plaques of a human genomic (leukocyte) library (CLONTECH) constructed in EMBL3 were screened by plaque hybridization with full-length ITI heavy chain cDNA probes labeled with 32 P by the random primer method. Hybridization was carried out as described by Maniatis et al (36).…”
Section: Screening Of the Human Genomic Library-10mentioning
confidence: 99%
“…31). The ITIH1 gene spans 14 kb and is composed of 22 exons (32). The ITIH4 * This work was supported by Association pour la Recherche sur le Cancer.…”
mentioning
confidence: 99%
“…The ITIHI chain is composed of 877 amino acid residues with a molecular mass of 92 kDa (Diarra-Mehrpour et al, 1992). The ITIHI gene spans about 14 kb and includes 22 exons with 15-281 bp in size (Bost et al, 1993). Three common alleles, ITIHI* 1, ITIHI*2 and ITIHI*3, are characterized by amino acid substitutions at positions 551 and 561 in exon 14 (Ding et al, 1995a).…”
mentioning
confidence: 99%
“…Oligonucleotide primer pairs for the amplification of 22 exons were designed from genomic sequence of ITIH1 gene (Bost et al, 1993) as shown in Table 1. Each exon was amplified by PCR mostly according to Thiberville et al (1994).…”
mentioning
confidence: 99%
See 1 more Smart Citation